Iowa RBA, February 15, 1999 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1999)
Email for the Iowa RBA for February 15, 1999. Highlights include Mountain Bluebird, Lesser Black-backed Gull, Long-tailed Duck, and Eurasian Collared Dove. Epson - sheet feed/flatbed